The Relationship Between Vitamin D Intake In Toddlers Aged 6–24 Months And The Severity Of Stunting - Baiq Viona Arij Inas Zahra; Lina Nurbaiti; Amelia Ramdani Hasby (CV. AFDIFAL MAJU BERKAH, 2026)
Stunting is one of the major nutritional problems in Indonesia, with a prevalence of 21.6% based on the 2022 Indonesian Nutritional Status Survey (SSGI). Vitamin D deficiency may contribute to impaired child growth and increased severity of stunting. To analyze the relationship between vitamin D intake and the severity of stunting among children aged 6–24 months in the working area of Bagu Public Health Center, Central Lombok Regency. Methods: T This study used a cross-sectional design involving 43 mothers with stunted and severely stunted toddlers selected through total sampling. Vitamin D intake was assessed using a 24-hour food recall method and analyzed with NutriSurvey 2007. Data were analyzed using Spearman’s Rank Correlation test with a significance level of α = 0.05. This study used a cross-sectional design involving 43 mothers with stunted and severely stunted toddlers selected through total sampling. Vitamin D intake was assessed using a 24-hour food recall method and analyzed with NutriSurvey 2007. Data were analyzed using Spearman’s Rank Correlation test with a significance level of α = 0.05. There was no significant relationship between vitamin D intake and the severity of stunting (p = 0.595; rₛ = 0.083). Most toddlers were aged 12 to <24 months (97.7%), male (58.1%), had received supplementary feeding programs (100%), and had a history of recurrent infections (67.4%). All toddlers had vitamin D deficiency (100%), with the main dietary sources derived from animal-based foods (74.4%). Vitamin D intake was not significantly associated with the severity of stunting among toddlers in the working area of Bagu Public Health Center, Central Lombok Regency.